Evaluasi User Experience Pada Game FORTNITE MOBILE Menggunakan Metode Enhanced Cognitive Walkthrough - Raka Irvaldo Rahadiasta; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
FORTNITE MOBILE is a competitive multiplayer game that makes "Battle-Royale" the main genre, this game is a type of Third-Person Shooter. This game was just released by Epic Games on July 24, 2018. This game includes a new type of game on the mobile platform so that it has the potential to have new users. User experience is very important for the success of a game on the market, especially on the type of application that has just been released. Systems that are not well designed and not easy to use will make it difficult for users to learn and operate, so it will rarely be used . In order to get a good user experience, an evaluation is necessary. Enhanced Cognitive Walkthrough method is a user experience evaluation method where evaluators provide scenario-based assignments and several questions to game users to find problems that interfere with the learning process. This method is suitable for the system that was just released because it can explore the cognitive processes of users when they first use the system. Respondents used in this study were divided into two groups, namely 3 respondents who had never played the FORTNITE MOBILE game and 3 people who were experienced in playing the FORTNITE MOBILE game and often played games with similar genres. The evaluation results on the FORTNITE MOBILE game show that many problems occur because the display does not explain its function (hidden) in the learn control menu. However, problems that arise are problems that are mild and do not affect the main functions in the game.